Hubungan Faktor Frekuensi Menyusui dengan Produksi Asi Pada Ibu Post Partum di RS SHL Pandeglang - Husmiati, Husmiati; Sukmawati, Sukmawati (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Exclusive breastfeeding coverage is still low both in the world, Indonesia and Banten province, the percentage of babies less than 6 months who receive exclusive breastfeeding in Pandeglang Regency is 19.88%, and there are still many postpartum mothers who do not understand the factors that influence breast milk production. To study the relationship between breastfeeding frequency factors and breast milk production at SHL Pandeglang Hospital in 2024. Analytical Survey, with a cross sectional approach, the population in this study were all 2nd day postpartum mothers who were at SHL Pandeglang Hospital in 2024 on 17 November to 25 December 2024 totaling 38 people, with a total sampling technique, using primary and secondary data, analysis using univariate and bivariate using chi square. From the results of univariate analysis: Of the 38 respondents, 9 respondents (23.7%) had poor breast milk production and 29 respondents (76.3%) had smooth breast milk production. Of the 38 respondents, 7 respondents (18.4%) had poor breastfeeding frequency and 31 respondents (81.6%) had good breastfeeding frequency. Bivariate analysis using the Chi Square statistical test revealed that there was a relationship between breastfeeding frequency and breast milk production at SHL Pandeglang Hospital in 2024, with ρ value = 0.000 and C value = 0.694, which means the relationship between frequency and breast milk production is in the very strong category.it is hoped that midwives in midwifery services can more intensively provide education on how to produce good breast milk, factors that influence breast milk production which can be done by breastfeeding babies as often as possible at least 8 times/day.  Keywords: Frequency Of Breastfeeding, Breast Milk Production  ABSTRAK Masih rendahnya cakupan ASI Eksklusif baik di Dunia, Indonesia maupun provinsi Banten, presentase bayi kurang dari 6 bulan yang mendapatkan ASI eksklusif  di Kabupaten Pandeglang adalah 19,88%, serta masih banyak ibu nifas yang belum mengerti faktor yang mempengaruhi produksi ASI. Untuk mempelajari Hubungan Faktor Frekuensi Menyusui dengan produksi ASI di RS SHL Pandeglang Tahun 2024. Survei Analitik, dengan pendekatan secara cross sectional, populasi dalam penelitian ini seluruh ibu nifas hari ke-2 yang berada di RS SHL Pandeglang Tahun 2024 pada tanggal 17 November s/d 25 Desember Tahun 2024 berjumlah 38 orang, dengan teknik total sampling, memakai data primer dan sekunder, analisis menggunakan univaariat dan bivariat menggunakan chi square. Dari hasil analisis univariat: Dari 38 responden sebanyak 9 responden (23,7%) produksi ASI tidak lancar dan sebanyak 29 responden (76,3%) produksi ASI lancar. Dari 38 responden sebanyak 7 responden (18,4%) frekuensi menyusui kurang dan sebanyak 31 responden (81,6%) frekuensi menyusui baik. Analisis bivariat dengan uji statsitik uji Chi Square diketahui ada hubungan frekuensi menyusui dengan produksi ASI di RS SHL Pandeglang Tahun 2024, dengan ρ value = 0,000 dan nilai C=0,694 yang artinya hubungan antara frekuensi dengan produksi ASI dengan kategori sangat kuat. Diharapkan bidan yang berada di pelayanan kebidanan  dapat lebih gencar melakukan edukasi bagaimana cara produksi ASI yang baik, faktor yang mempengaruhi produksi ASI yang dapat dilakukan dengan menyusui bayi sesering mungkin minimal 8 kali/hari.  Kata Kunci: Frekuensi Menyusui, Produksi ASI